THE SPIRIT OF RECIPROCITY VERSES IN THE QURAN AS A SOLUTION TO COUNTER RELIGIOUS RADICALISM - Kamal, Muhamad Ali Mustofa (Teosofia: Indonesian Journal of Islamic Mysticism, 2019)
The diversity of religions necessitates the recognition and respect of religions other than ours. Islam is a religion that is peaceful and full of love. The spread of radicalism in religious communities in Indonesia illustrates the lack of tolerance in the recognition of religious diversity and the religious diversity of others. This literary research uses a qualitative approach with content analysis and comprehensive interpretation for the Qur'anic text about reciprocity verses. This study concludes that the Qur'an provides enthusiasm and solutions in terms of management and counteracts religious radicalism in the spirit of 'mutual'. Recitation of reciprocal verses as illustrated by the Quran with the editorial and unique arrangement of language in the al-Nisa’ verse 86 and al-An'am verse 108 provides a 'mutual' solution. The principle of mutual respect (al-Nisa ': 86) and not berating each other (al-An'am: 108) with a better attitude in religious life.